How important is China for the US exchange rate and current account? - Almira Buzaushina (Verein für Socialpolitik, 2010)
The purpose of this paper is to investigate New Open Economy Macroeconomics in an empirical way in order to analyze the ability of these models in explaining key variables: exchange rate and current account. A standard two-country dynamic stochastic general equilibrium model with nominal rigidities and imperfect competition is estimated using the maximum likelihood procedure. In contrast to previous literature, the estimation methods are fitted to the data of the USA and its main trading partners, including China and Mexico. The estimation results show that the consideration of the data for these countries on the opposite side of the US is important for explaining the US current account and exchange rate movements, as well as for getting confident estimates for some deep parameters which are controversial in the theoretical literature.
Keywords: F00; F41; F40; 330; New Open Economy Macroeconomics; Maximum Likelihood Estimation